A nondestructive testing method for martensitic transformation in austenitic stainless steel
By establishing a model of martensite transformation and hysteresis loop curves in austenitic stainless steel, the problem that martensite transformation detection in the prior art cannot be achieved without non-destructive detection, and fast and lossless The testing has a wide range of applications and is suitable for a large number of rapid testing needs.
Patent Information
- Application Number
- CN202210952585.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-09
AI Technical Summary
The prior art cannot realize non-destructive testing of martensite transformation in austenitic stainless steel, and the testing equipment is bulky, complex in operation, long detection time and high professionalism.
By establishing a martensite transformation and hysteresis loop curve model, the hysteresis loop curve of the austenite stainless steel to be measured, and combining the data measured by the X-ray diffractometer, the martensite transition variable is obtained. This method does not require sampling and polishing, it is simple to operate and has a small footprint for the equipment.
It realizes rapid and non-destructive testing of martensite transformation in austenitic stainless steel, reduces the testing time and professional requirements, has a wide range of application, and can meet a large number of fast testing needs.
Smart Images

Figure CN115436461B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel, and in particular to a nondestructive detection method for martensitic transformation amount in austenitic stainless steel. Background Art
[0002] China is a major steel manufacturer and user, and steel is used in all areas of life. Austenitic stainless steel, a type of steel that has been produced and used in large quantities, is the most widely used type of stainless steel. Austenitic stainless steel is corrosion-resistant and oxidation-resistant, and has excellent mechanical properties and good welding properties in a wide temperature range, and is widely used in the engineering field.
[0003] Among them, austenitic 304 stainless steel has the largest application volume, but the main structure of austenitic 304 stainless steel at room temperature is metastable austenite structure, and the yield strength is low. It is usually improved by cold working deformation and other methods. During the plastic deformation process at room temperature, the metastable austenite structure is prone to martensitic phase transformation to form body-centered cubic martensite with ferromagnetism, which greatly affects the plastic deformation ability, work hardening behavior and mechanical properties of austenitic stainless steel. After the martensitic transformation of austenitic stainless steel, the plastic deformation ability of austenitic stainless steel will be weakened, and stress corrosion will be more likely to occur. In actual production and life, there have been many accidents caused by stress corrosion of austenitic stainless steel. The direct reason is that the deformation of austenitic stainless steel during use induces martensitic transformation, which leads to local stress corrosion of austenitic stainless steel.
[0004] The existing method for detecting the amount of martensitic transformation in austenitic stainless steel generally uses XRD for measurement. However, the use of XRD requires sampling on the sample to be tested and professional polishing of the sample, which is time-consuming and labor-intensive. In addition, XRD diffraction test equipment is expensive, occupies a large area, is complex to operate, has very high professional requirements for testers, and takes a long time to test. It cannot meet the growing demand for the detection of martensitic transformation in austenitic stainless steel.
[0005] Therefore, technicians in this field are committed to developing a non-destructive detection method for the amount of martensitic transformation in austenitic stainless steel to address the deficiencies of the above-mentioned prior art. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is that in the prior art, the transformation amount of martensite in austenitic stainless steel cannot be detected by non-destructive testing, the detection equipment is bulky, the operation is complicated, the detection is too professional, and the detection time is long.
[0007] To achieve the above object, the present invention provides a nondestructive detection method for the martensitic transformation amount in austenitic stainless steel, comprising the following steps:
[0008] Step 1, establishing a martensitic transformation amount and hysteresis loop curve model;
[0009] Step 2, measuring the hysteresis loop curve of the austenitic stainless steel to be tested;
[0010] Step 3: According to the relevant data of steps 1 and 2, the martensitic transformation amount of the austenitic stainless steel to be tested can be obtained;
[0011] The basis for establishing the model in step 1 is that austenite itself has no magnetism, but during the cold deformation process, the original austenite structure will undergo cold deformation-induced martensitic phase transformation, and the martensite content produced by the deformation will change to a certain extent with the change of the cold deformation amount, so that the austenitic stainless steel will have a certain magnetism;
[0012] The model establishment in step 1 requires using an X-ray diffractometer to measure the martensite transformation amount of austenitic stainless steel;
[0013] The model establishment in step 1 requires the use of a BH tester to measure the hysteresis loop curve model of austenitic stainless steel;
[0014] There is a certain functional relationship between the martensite transformation amount in step 1 and the hysteresis loop curve of austenitic stainless steel;
[0015] The establishment of the model in step 1 requires a certain amount of data support;
[0016] Furthermore, in order to establish the model in step 1, it is necessary to first sample the austenitic stainless steel, and the sampling needs to ensure that the surface of the sample is free of oil and rust and is relatively smooth and flat; then the martensitic transformation amount of the austenitic stainless steel is accurately measured by an X-ray diffractometer; after the X-ray diffractometer measurement is completed, the relevant hysteresis loop data is collected;
[0017] Furthermore, in step 1, the X-ray diffractometer irradiates a beam of monochromatic X-rays into the crystal, and the wavelength of the incident X-rays is in the same order of magnitude as the distance between the regularly arranged atoms. Since the X-rays scattered by different atoms interfere with each other, strong X-ray diffraction will occur in certain special orientations, so a strong diffraction peak will be generated. The crystal structure is closely related to the intensity and orientation of the diffraction line in space, so the diffraction peak of martensite can be inferred, and then according to the cumulative intensity of the diffraction line of the martensite crystal plane, the cumulative intensity of the diffraction line of the austenite crystal plane, the volume fraction of the total amount of carbides, the volume fraction of the austenite phase, and the intensity factor corresponding to the austenite crystal plane and the martensite crystal plane; the volume fraction of martensite in austenitic stainless steel, that is, the martensite transformation amount, can be obtained, and the specific calculation formula is V A=(1-V C ) / (1+G(I M / I A )); where V A is the volume fraction of austenite phase in austenitic stainless steel; V C is the volume fraction of the total amount of carbides in austenitic stainless steel; I M It is the cumulative intensity of the diffraction lines of the martensite crystal plane in austenitic stainless steel measured by X-ray diffractometer; I A is the cumulative intensity of the diffraction lines of the austenite crystal plane in austenitic stainless steel measured by an X-ray diffractometer; G is the intensity factor corresponding to the austenite crystal plane and the martensite crystal plane;
[0018] Furthermore, in step 1, function fitting can be performed based on the above two data to obtain a functional relationship between the martensite transformation amount of austenitic stainless steel of a certain constant composition and its hysteresis loop curve;
[0019] Step 2, measuring the hysteresis loop curve of the austenitic stainless steel to be tested;
[0020] The hysteresis loop curve obtained in step 2 can interpret the nonlinear relationship between the magnetic field intensity H, the magnetization intensity M and the magnetic induction intensity B;
[0021] The specific operation of measuring the hysteresis loop curve of austenitic stainless steel in step 2 is as follows: placing the austenitic stainless steel sample to be tested into the BH tester and turning on the power supply, a magnetic field will be generated in the working area of the tester, and the austenitic stainless steel to be tested will be magnetized, and the magnetization intensity is M. The magnetic induction intensity B generated by the material can be expressed by the formula B=μ0(H+M); μ0 represents the vacuum magnetic permeability;
[0022] After the measuring instrument starts working in step 2, the current on the primary coil of the measuring instrument continues to increase, and the electromagnetic flux meter will detect the corresponding magnetic flux, thereby obtaining the BH curve of the sample. When H continues to increase, B will tend to saturation, and then the external magnetic field will continue to decrease. If the sample has magnetic conductivity, the M or B value will not return along the path of the initial magnetization curve;
[0023] Then increase the magnetic field in the opposite direction. When the external magnetic field is 0, record the remanent magnetization B. r With M r ; Continue to increase the magnetic field in the opposite direction, M or B continues to decrease; when the reverse magnetic field reaches a certain value, M = 0 or B = 0, then record the coercive force M H C or B H C ;
[0024] At this time, the reverse magnetic field becomes larger, and the magnetic induction intensity or magnetization or direction in the sample also begins to reverse; as the reverse magnetic field becomes larger, M or B gradually saturates in the reverse direction; finally, the external magnetic field H returns from the negative maximum to the positive maximum and repeats this process to record two closed curves of MH and BH;
[0025] Furthermore, the hysteresis loop curve measurement in step 2 does not require sampling or sample preparation of the austenitic stainless steel. It is only necessary to ensure that the surface of the austenitic stainless steel to be tested does not have impurities that affect the hysteresis measurement.
[0026] The operator only needs to put the austenitic stainless steel to be tested into the test chamber, and the BH tester will automatically complete the specific operation steps.
[0027] Furthermore, the hysteresis loop curve measurement in step 2 can obtain the remanence and magnetic permeability of the austenitic stainless steel;
[0028] Step 3, according to the relevant data of steps 1 and 2, the martensite transformation amount of the austenitic stainless steel to be tested can be obtained; according to the martensite transformation amount and hysteresis loop curve model established in step 1, combined with the hysteresis loop curve measured in step 2, the remanence and magnetic permeability of the austenitic stainless steel to be tested can be obtained according to the hysteresis loop curve, and combined with the model data obtained in step 1, the martensite transformation amount in the austenitic stainless steel can be obtained;
[0029] The step 3 completes a non-destructive test of the martensite transformation amount in austenitic stainless steel;
[0030] By adopting the above scheme, the nondestructive detection method of martensitic transformation amount in austenitic stainless steel disclosed in the present invention has the following advantages:
[0031] (1) The nondestructive detection method of the martensitic transformation amount in austenitic stainless steel of the present invention can solve the determination of the transformation amount of austenitic stainless steel in a large number of practical engineering applications through the established model data; and the operation of the measuring instrument is simple, and the test personnel do not need to have deep professional knowledge, and the difficulty of getting started is low. It can be widely promoted and used, and the detection speed is fast, which can meet the rapid determination of the martensitic transformation amount of austenitic stainless steel in a large number of cases;
[0032] (2) The nondestructive detection method of the martensitic transformation amount in austenitic stainless steel of the present invention does not require the preparation of samples in advance, and the whole process is nondestructive detection. The measuring instrument occupies a small area and has a certain degree of portability.
[0033] In summary, the nondestructive detection method for the martensitic transformation amount in austenitic stainless steel disclosed in the present invention does not require advance sample preparation and can perform nondestructive testing throughout the entire process. In addition, the detection equipment occupies a small area, has low difficulty in operation, has a wide range of applications, and has a fast detection speed, and can meet the needs of a large number of rapid determinations of the martensitic transformation amount of austenitic stainless steel.
[0034] The concept, specific technical scheme and technical effects of the present invention will be further described below in conjunction with specific implementation methods to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a function fitting diagram of the present invention with the martensite transformation amount as the horizontal coordinate and the austenitic stainless steel magnetic susceptibility as the vertical coordinate;
[0036] Figure 2 It is the BH hysteresis loop diagram of the austenitic stainless steel to be tested in the patent of the present invention. DETAILED DESCRIPTION
[0037] The following introduces several preferred embodiments of the present invention to make its technical content clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, which are exemplary descriptions, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0038] Example: Testing of austenitic stainless steel products produced by a factory
[0039] The factory mainly produces chromium-nickel austenitic stainless steel, which is mainly used for pipeline transmission in the chemical industry. The raw materials of chromium-nickel austenitic stainless steel are easy to obtain, easy to process, low in cost, good in oxidation resistance, and have excellent mechanical properties and good welding properties. It is an ideal chemical pipeline transmission material. However, if austenitic stainless steel undergoes martensitic transformation during long-term use, it will be more prone to stress corrosion. Most accidents in actual engineering applications are related to this. Therefore, it is necessary to ensure that the martensitic transformation of the chromium-nickel austenitic stainless steel produced is low enough and has a good ability to prevent stress corrosion. In the subsequent use process, stress corrosion will not cause the failure of austenitic stainless steel.
[0040] First, step 1 is performed to establish a martensitic transformation amount and hysteresis loop curve model for the chromium-nickel austenitic stainless steel produced by the factory;
[0041] Austenitic stainless steel is very likely to induce martensitic phase transformation after deformation. After martensitic transformation occurs in austenitic stainless steel, there is an obvious corresponding relationship between the magnetic field intensity distribution characteristics on its surface and the amount of martensitic transformation. The change in the surface magnetic field intensity of austenitic stainless steel can reflect the martensitic transformation in austenitic stainless steel. This is the theoretical basis for establishing the model of martensitic transformation amount and hysteresis loop curve.
[0042] First, a sample of austenitic stainless steel was cut and sampled. A sample of 200mm*200mm*50mm was cut to ensure that there was no oil, rust or impurities on the surface of the sample. The surface of the sample was polished as smooth as possible and then placed in an X-ray diffractometer for ray scanning.
[0043] The X-ray diffractometer shoots a beam of monochromatic X-rays into the crystal. The wavelength of the incident X-rays is in the same order of magnitude as the distance between these regularly arranged atoms. Since the X-rays scattered by different atoms interfere with each other, strong X-ray diffraction will occur in certain special orientations, so strong diffraction peaks will be produced. The crystal structure is closely related to the intensity and orientation of the diffraction lines in space, so the diffraction peak of martensite can be inferred. Based on the cumulative intensity of the diffraction lines of the martensite crystal plane, the cumulative intensity of the diffraction lines of the austenite crystal plane, the volume fraction of the total amount of carbides, the volume fraction of the austenite phase, and the intensity factors corresponding to the austenite crystal plane and the martensite crystal plane, the volume fraction of martensite in austenitic stainless steel, that is, the martensite transformation amount, can be obtained. The specific calculation formula is V A =(1-V C ) / (1+G(I M / I A ));
[0044] In the formula, V A is the volume fraction of austenite phase in austenitic stainless steel; V C is the volume fraction of the total amount of carbides in austenitic stainless steel; I M It is the cumulative intensity of the diffraction lines of the martensite crystal plane in austenitic stainless steel measured by X-ray diffractometer; I A is the cumulative intensity of the diffraction lines of the austenite crystal plane in austenitic stainless steel measured by an X-ray diffractometer; G is the intensity factor corresponding to the austenite crystal plane and the martensite crystal plane;
[0045] Substituting the data after diffraction by the X-ray diffractometer into the above formula, the amount of martensitic transformation of the austenitic stainless steel can be obtained;
[0046] In this specific implementation, the specific parameters of the X-ray diffractometer are set as follows: the scanning angle range is 10°-90°, the step size is set to 4° / min, the tube voltage is set to 40kv, and the tube current is set to 20mA;
[0047] After the martensitic transformation amount is recorded, the hysteresis loop curve of the austenitic stainless steel with the same martensitic transformation amount is collected; after the operator puts the austenitic stainless steel with the measured specific martensitic transformation amount into the MH measuring instrument and completes the operation according to the prompts, the measuring instrument will automatically generate the hysteresis loop curve of the austenitic stainless steel;
[0048] Then repeat the above operation on the austenitic stainless steel of the plant to measure its transformation martensite amount and hysteresis loop curve; more data can be obtained to better improve the model and make the fitted function closer to the actual situation; and for chromium-nickel austenitic stainless steel of the same formula, several types with larger differences in martensite transformation amount should be adopted;
[0049] This specific implementation mainly adopted 6 representative data, as follows Figure 1 As shown; wherein the abscissa is the martensitic transformation amount first measured in step 1, and the ordinate is the magnetic susceptibility of the austenitic stainless steel subsequently measured in step 1;
[0050] After completing the establishment of the relevant model for the chromium-nickel austenitic stainless steel produced by the factory, the next step can be carried out, which is to conduct non-destructive testing on the martensitic transformation of the austenitic stainless steel produced by the factory, that is, to measure the hysteresis loop curve of the austenitic stainless steel to be shipped out of the factory;
[0051] The implementation of step 2 does not require the operator to have professional subject knowledge, and only requires simple operation training before taking up the post;
[0052] The tester puts the austenitic stainless steel to be tested into the BH tester. After the power is turned on, a magnetic field will be generated in the working area of the tester, and the austenitic stainless steel to be tested will be magnetized with a magnetization intensity of M. The magnetic induction intensity B generated by the material can be expressed by the formula B = μ0 (H + M); where μ0 represents the vacuum magnetic permeability;
[0053] When the measuring instrument starts working, the current on the primary coil of the measuring instrument continues to increase, and the electromagnetic fluxmeter will detect the corresponding magnetic flux, thereby obtaining the BH curve of the sample. When H continues to increase, B will tend to saturation, and then the external magnetic field will continue to decrease. If the sample has magnetic conductivity, the M or B value will not return along the path of the initial magnetization curve;
[0054] Then the measuring instrument will increase the magnetic field in the opposite direction. When the external magnetic field is 0, the residual magnetism B is recorded. r With M r ; Continue to increase the magnetic field in the opposite direction, M or B continues to decrease. When the reverse magnetic field reaches a certain value, M = 0 or B = 0 is satisfied, then the coercive force is recorded. M H C or B H C;
[0055] At this time, the reverse magnetic field becomes larger, and the magnetic induction intensity or magnetization or direction in the sample also begins to reverse. As the reverse magnetic field becomes larger, M or B gradually saturates in the reverse direction. Finally, the external magnetic field H is returned from the maximum negative value to the maximum positive value and this process is repeated to record the two closed curves of MH and BH. The entire test process takes less than 2 minutes.
[0056] Then, step 3 is performed, and the martensitic transformation amount of the austenitic stainless steel to be tested can be obtained according to the relevant data of steps 1 and 2;
[0057] The hysteresis loop curve measured in this specific implementation method is as follows: Figure 2 As shown, combined with the martensitic transformation amount and hysteresis loop curve model established in step 1, and the hysteresis loop curve of the austenitic stainless steel to be tested obtained in step 2, the remanence and magnetic permeability of the austenitic stainless steel to be tested can be interpreted from the data obtained in step 2, and substituted into the model established in step 1, the martensitic transformation amount of the austenitic stainless steel to be tested can be obtained by fitting the function, and it is calculated that the magnetic susceptibility of the austenitic stainless steel to be tested in step 2 is 0.002T, and the magnetic permeability is 1.2, showing a strong magnetic conductivity; through the fitting function, it can be known that the martensitic transformation amount of the austenitic stainless steel to be tested is 30%. After completing the above steps, a non-destructive test of the martensitic transformation amount in austenitic stainless steel is completed.
[0058] The BH test takes 2 minutes, and it takes 1 minute to substitute the martensitic transformation amount and the hysteresis loop curve model to obtain the martensitic transformation amount. The total time for non-destructive testing is 3 minutes.
[0059] Comparative Example 1: Using traditional methods to detect the amount of martensite transformation in austenitic stainless steel
[0060] Cut a 100mm*100mm*20mm sample from the sample to be tested, which takes 3 minutes; then grind the sample to make it smooth and flat, and make sure that there is no oil, rust or impurities on the surface of the sample as much as possible, which takes 5 minutes; then place the polished sample into the X-ray diffractometer, the scanning angle range of the X-ray diffractometer is: 10°-90°, the scanning step is 4° / min, and the scanning takes a total of 20 minutes; after the scanning is completed, the XRD diffraction peak diagram is presented on the computer, and professional technicians obtain relevant diffraction peak information by consulting the PDF card, and substitute it into the calculation. Professionally trained technicians perform accurate calculations, which takes 4 minutes;
[0061] Finally, comparative example 1 used the traditional method to detect the amount of martensite transformation in austenitic stainless steel, which took a total of 32 minutes.
[0062] Result analysis: Through the analysis and comparison between Example 1 and Comparative Example 1, it can be known that after the model is established in Example 1, the detection of the martensitic transformation amount in austenitic stainless steel can be completed in a very short time. Compared with the traditional detection method, the detection method of the patent of the present invention saves about 1000% of the time. The time consumed by the traditional detection of one sample can be used to detect 10 samples by the method of the patent of the present invention, achieving efficiency crushing on an order of magnitude.
[0063] In summary, the technical solution of this patent, by establishing a correlation model between the martensitic transformation amount and the hysteresis loop curve in advance, has achieved an order of magnitude crushing of the traditional detection efficiency in the actual engineering method of measuring the transformation amount of austenitic stainless steel, and the detection equipment occupies a small area and has a certain degree of portability; there is no need to prepare samples in advance, and non-destructive testing is achieved. The method is easy to use, has low professional requirements for testers, and has a wide range of application, which can meet the rapid determination of the martensitic transformation amount of austenitic stainless steel in large quantities.
[0064] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A nondestructive detection method for martensitic transformation in austenitic stainless steel, characterized in that: The steps include: Step 1, establishing a martensitic transformation amount and hysteresis loop curve model; Step 2, measuring the hysteresis loop curve of the austenitic stainless steel to be tested; Step 3: According to the relevant data of steps 1 and 2, the martensitic transformation amount of the austenitic stainless steel to be tested can be obtained; The more data collected by the martensitic transformation and hysteresis loop curve models, the more accurate the resulting models will be. The model establishment in step 1 requires using an X-ray diffractometer to measure the martensite transformation amount of austenitic stainless steel; The model establishment in step 1 requires the use of a BH tester to measure the hysteresis loop curve model of austenitic stainless steel; There is a certain functional relationship between the martensite transformation amount in step 1 and the austenitic stainless steel hysteresis loop curve. After data collection, function fitting is performed.
2. The nondestructive testing method according to claim 1, characterized in that: To establish the model in step 1, it is necessary to first sample austenitic stainless steel. The sampling needs to ensure that the surface of the sample is free of oil and rust and is relatively smooth and flat; The amount of martensite transformation of austenitic stainless steel was then accurately measured using an X-ray diffractometer; After the X-ray diffractometer measurement is completed, the relevant hysteresis loop data will be collected.
3. The nondestructive testing method according to claim 1, characterized in that: The hysteresis loop curve measurement in step 2 does not require sampling or sample preparation of the austenitic stainless steel. It is only necessary to ensure that the surface of the austenitic stainless steel to be tested is free of impurities that may affect the hysteresis rate measurement.
4. The nondestructive testing method according to claim 1, characterized in that: In step 3, the remanence and magnetic permeability of the austenitic stainless steel to be tested can be obtained according to the loop curve based on the martensitic transformation amount and hysteresis loop curve model established in step 1 and the hysteresis loop curve measured in step 2. By comparing the model data, a non-destructive test of the martensitic transformation amount in the austenitic stainless steel is completed.
5. The nondestructive testing method according to claim 1, characterized in that: In step 1, the formula for calculating the martensite transformation amount is V A =(1-V C ) / (1+G(I M / I A )); where V A is the volume fraction of austenite phase in austenitic stainless steel; V C is the volume fraction of the total amount of carbides in austenitic stainless steel; I M It is the cumulative intensity of the diffraction lines of the martensite crystal plane in austenitic stainless steel measured by X-ray diffractometer; I A It is the cumulative intensity of the diffraction lines of the austenite crystal plane in austenitic stainless steel measured by an X-ray diffractometer; G is the intensity factor corresponding to the austenite crystal plane and the martensite crystal plane.
6. The nondestructive testing method according to claim 1, characterized in that: The specific operation of measuring the hysteresis loop curve of austenitic stainless steel in step 2 is as follows: placing the austenitic stainless steel sample to be tested into the BH measuring instrument and turning on the power supply, a magnetic field will be generated in the working area of the measuring instrument, and the austenitic stainless steel to be tested will be magnetized, and the magnetization intensity is M, μ0 represents the vacuum magnetic permeability, and the magnetic induction intensity B generated by the material can be expressed by the formula B=μ0(H+M).
Citation Information
Patent Citations
Method and device for measuring residual austenite quantity in steel
JP2003090825A